AI Hallucination dalam Pembelajaran Aljabar : Systematic Literature Review untuk Berpikir Kritis dan Literasi Numerasi - Filda Indriya Laili; Wahyudi; Dwi Avita Nurhidayah (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2026)
The use of Artificial Intelligence (AI) without careful evaluation can lead to cognitive dependency and diminish students’ critical thinking skills. One emerging phenomenon is AI hallucination. This study highlights the dual role of AI hallucinations as both a cognitive risk and a pedagogical opportunity to enhance students’ critical thinking skills and numeracy literacy. The method employed is a Systematic Literature Review (SLR) using the PRISMA framework. Data were analyzed using thematic analysis techniques on articles from the Google Scholar, ERIC, and DOAJ databases published between 2021 and 2026. The search process yielded 842 articles, which were then selected based on inclusion and exclusion criteria, resulting in 21 relevant articles. Research findings indicate that AI hallucinations can be used as a reflective learning tool, encouraging students to identify errors, evaluate solution steps, and reconstruct their mathematical understanding. This process contributes to improved critical thinking skills, strengthens conceptual understanding of algebra, and enhances students’ numeracy literacy. Therefore, AI is not merely a tool but also a pedagogical instrument that supports analytical and evaluative learning. This research implies the need for a transformation in mathematics teaching practices, where educators no longer position AI as a provider of instant answers but rather make it the subject of critical evaluation through instructional designs that require students to actively verify their work